Upaya Meningkatkan Kemampuan Membaca MelaluiBermain Kartu Huruf Pada Anak Usia 5-6 TahunKelompok B Tk Pertiwi Seso KecamatanJepon Kabupaten BloraTahun 2015/2016 - MULYANI, MULYANI; , Dr. Darsinah, M. Si (2015)
This study aims to improve the reading skills of children through letters card. This research is a classroom action research conducted in two cycles and each cycle outsmart conducted two meetings. The subjects of this study is children Group B TK Pertiwi Seso District of Jepon Blora totaling 13 children as recipients of actions, researcher and teacher colleagues as giving action. The data collected in this study is the ability to read data on children and data on teacher learning through letters card. Both of these data were collected through observation. Data were analyzed with the child's ability to read and comparative analysis of data on teacher learning through letter cards analyzed by interactive analysis. The results of the analysis showed that the average prasiklus reading ability of 57% means that the ability to read the new kid growing as expected. After the first cycle measures the average reading skills of children reached 73%, which means that the developing child's reading ability was as expected, but already there is an increase. After the second cycle measures the average reading ability increased by 88% means that the reading skills of children develop very baik. Main of this study is that through the letter cards can improve reading ability of children in group B TK Pertiwi Seso District of Jepon Blora.